General Deficit in Inhibitory Control of Excessive Smartphone Users: Evidence from an Event-Related Potential Study - Chen, Jingwei; Liang, Yunsi; Mai, Chunmiao; Zhong, Xiyun; Qu, Chen (Frontiers in Psychology, 2016)
With the popularity of smartphones, the problem of excessive use has drawn increasing attention. However, it is not clear whether there is an inhibitory deficit in excessive smartphone users. Using a modified Go/NoGo task with three types of context (blank, neutral and smartphone-related), the present study combined measures of behavior and electrophysiology (event-related potentials, ERPs) to examine general and specific inhibitory control in an excessive smartphone use group and a normal use group. Results showed that participants in both groups had larger amplitude of N2 and P3 on NoGo trials than Go trials. NoGo N2, an ERP component associated with inhibitory control, was more negative in the excessive smartphone use group than the normal use group. These results suggest that in the early stage of inhibition processing, excessive smartphone users experience more conflicts and show a general deficit that does not depend on smartphone-related cues. Moreover, the study provides further neuroscience evidence of the physiological correlates of excessive smartphone use.